Web-based Information System for Research and Community Service (PkM) Submissions at LPPM, Nahdlatul Ulama University Lampung - Rudi Hartono; Kusuma Wardany (Universitas Islam Indragiri, 2026)
Management of research and community service (PkM) activities in higher education institutions requires an integrated information system to enhance the effectiveness, transparency, and accountability of processes. The LPPM at Nahdlatul Ulama University Lampung still faces challenges in managing proposal submissions, reviewer assignments, the review process, and the handling of research and PkM reports, which are not yet fully integrated into a single system. This study aims to develop and implement a web-based Research and PkM Submission System for LPPM at Nahdlatul Ulama University Lampung. The research adopts the Waterfall model, covering the stages of analysis, design, implementation, testing, and maintenance. The system is built using PHP and MySQL, supported by HTML, CSS, and Bootstrap technologies. To ensure functionality meets the specified requirements, verification was conducted using Blackbox Testing. In addition to functional testing, application performance was evaluated by measuring system response times for login, proposal storage, document uploads, and dashboard display on both desktop and mobile devices. Test results indicate that the platform responds within an average of 1–3 seconds for key functions and demonstrates stable performance without technical issues throughout the testing period. The findings show that the application successfully integrates the entire workflow of proposal submission, reviewer assignment, proposal and report review processes, and monitoring of research and PkM status into a single platform. Testing results confirm that all system modules function correctly and align with the testing scenarios. Therefore, this system is considered suitable for implementation as a supporting management tool for research and PkM activities at LPPM Nahdlatul Ulama University Lampung